'They patiently heard what we had to say…this felt different to me': the palliative care needs and care experiences of advanced cancer patients and their families in Bangladesh. Issue 2 (1st June 2012) - Dehghan, Rogieh; Ramakrishnan, Jairam; Uddin-Ahmed, Nezzan; Harding, Richard
Abstract : Background: In 2008, 70% of cancer deaths occurred in low- and middle-income countries. This study aimed to describe the needs and experiences of patients and families who received palliative care in Bangladesh, and those of the providing clinicians, in order to inform fledgling service development. Methods: Patients, family members and specialist palliative care physicians (n=20) participated in a cross-sectional semistructured qualitative study. Following peer review of coding units, relational codes were established and a resulting frame constructed. Results: The data fit well within the existing domains of palliative care, as respondents described the family-wide distress and impact of the disease, psychological, physical and social problems. However, the contextual experience of cancer in this setting revealed particular challenges, as respondents described anger, helplessness and mistrust towards existing (non-palliative) healthcare. Poor patient–doctor communication and unmet need for information contributed greatly to these poor experiences. By contrast, experience of palliative care was explained in radically different terms, with a clear shift in the nature of the interaction and resulting care, to bring effective communication and relief from suffering. Conclusion: To alleviate the distress to cancer patients and their families, it is essential for oncologists to receive adequate training in palliative care, especially in communication, holistic assessment and information giving. To meet the massive challenge in a country like Bangladesh, palliative care should be mainstreamed into the existing healthcare system for a feasible and sustainable public health approach.